Enabling mātauranga‐informed management of the Kaipara Harbour, Aotearoa New Zealand - Maria Hepi; Jeffrey Foote; Leane Makey; Monique Badham; Alyssce Te Huna (New Zealand Journal of Marine and Freshwater Research, 2018)
The Integrated Kaipara Harbour Management Group (IKHMG) promotes the integrated management, inter‐agency coordination and kaitiakitanga of the Kaipara Harbour and its catchment. Led by the hapū (subtribe) Te Uri o Hau, the group is a collective of stakeholders and community. In 2013, the Institute of Environmental Science and Research (ESR) and Te Uri o Hau examined the IKHMG to understand what enables and hinders mātauranga‐informed management of the Kaipara Harbour. A review of literature relating to mātauranga and environmental resource management found a myriad of issues in integrating indigenous knowledge with science, or with indigenous knowledge holders working with scientists and/or resource managers. Our cross‐cultural collaborative research examined to what extent the IKHMG overcame these issues and incorporated mātauranga into planning and decision‐making. We make the case that the challenge facing cross‐cultural integrated catchment programmes should not be so much ‘how to integrate indigenous knowledge into resource management’ but ‘how to integrate indigenous knowledge holders into planning and decision‐making’ to enable indigenous knowledge holders to articulate management in their own terms as an expression of self‐determination.